Trends of staple food and input prices: Global and regional overview, 2007-2010 - Wanjiku, J.; Wambua, J.; Karugia, Joseph T. (Association for Strengthening Agricultural Research in Eastern and Central Africa, 2011)
This policy brief is the fifth in a series of quarterly briefs that provide updates on the food price situation in the Eastern and Southern Africa (ESA) region. The briefs are a follow up of an earlier study on the impact of rising food prices in the ESA region that was carried out by the Association for Strengthening Agricultural Research in East and Central Africa (ASARECA) in collaboration with the Regional Strategic Analysis and Knowledge Support System for Eastern and Central Africa (ReSAKSS-ECA) and the Consultative Group on International Agricultural Research (CGIAR) Alliance. The first update focused on the food price trends in ESA and their relationship with global food prices. The second update discussed policy responses to the food price crisis in ESA region. The third update focused on the relationships between the prices of staple foods and those of non-tradable foods (orphan crops), while the fourth brief discussed the linkages between the prices of agricultural inputs and output. This brief looks at the trend of the staple food prices, both global and national, over the period 2007-2010 and presents the price trends of inputs (fertilizer and fuel) over the same period. It also discusses the status of food prices before and after the food price crisis of 2008. Have the food prices continued to soar after the 2008 food price crisis? What is the effect of the drought in Russia and Thailand and the flooding in Pakistan on global and regional food prices?